2005
DOI: 10.1097/00000542-200505000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Duration of Preoperative Smoking Cessation to Improve Wound Healing after Head and Neck Surgery

Abstract: Preoperative smoking abstinence of longer than 3 weeks reduces the incidence of impaired wound healing among patients who have undergone reconstructive head and neck surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
110
1
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(116 citation statements)
references
References 17 publications
2
110
1
3
Order By: Relevance
“…1). There were seven prospective cohort studies, 12,[20][21][22][23][24][25] 16 retrospective cohort studies, [26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41] and two RCTs (Table 1). 42,43 Both RCTs offered nicotine replacement therapy.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1). There were seven prospective cohort studies, 12,[20][21][22][23][24][25] 16 retrospective cohort studies, [26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41] and two RCTs (Table 1). 42,43 Both RCTs offered nicotine replacement therapy.…”
Section: Resultsmentioning
confidence: 99%
“…42,43 Both RCTs offered nicotine replacement therapy. 42,43 There were 14 studies from North America, 12,21,23,26,[30][31][32][33][34][35]37,[39][40][41] six from Europe, 22,27,28,38,42,43 four from Asia, 20,25,29,36 and one from Australia. 24 There were more male than female smokers, and smokers were younger than non-smokers or ex-smokers in many of the studies.…”
Section: Resultsmentioning
confidence: 99%
“…Smoking appears to suppress the immune system [18]. It was found that the percentage of impaired wound healing was greater in nonsmokers than individuals who had not smoked for more than 22 days (47% nonsmokers versus 67%, p\0.05) after head and neck surgery [11]. A risk reduction of 19% is seen for each week of cessation before surgery [19].…”
Section: Discussionmentioning
confidence: 99%
“…Smokers have a higher incidence of postoperative pulmonary complications than non-smokers, 1 and smoking is associated with impaired wound healing and increased incidence of infection. 2,3 Hospitalization and the period of forced cessation it entails is often characterized as a ''window of opportunity'' for delivering cessation interventions. 4,5 Hospital-based smoking cessation interventions are effective, and even brief advice delivered by a health professional can enhance quit rates.…”
Section: Résumémentioning
confidence: 99%